2004
DOI: 10.1086/422982
|View full text |Cite
|
Sign up to set email alerts
|

Copycat Funds: Information Disclosure Regulation and the Returns to Active Management in the Mutual Fund Industry

Abstract: Mutual funds must disclose their portfolio holdings to investors semiannually. The costs and benefits of such disclosures are a long-standing subject of debate. For actively managed funds, one cost of disclosure is a potential reduction in the private benefits from research on asset values. Disclosure provides public access to information on the assets that the fund manager views as undervalued. This paper tries to quantify this potential cost of disclosure by testing whether "copycat" mutual funds, funds that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(63 citation statements)
references
References 15 publications
3
60
0
Order By: Relevance
“…Alternatively, other investors could mimic, with a lag, the positions of the best-performing funds. Notably, Frank, Poterba, Shackelford, and Shoven (2004) demonstrated that copycat portfolios that mimic the disclosed positions of mutual funds generate static returns that are similar to the returns of the actual funds. Wermers, Yao, and Zhao (2007) also found substantial excess returns, even beyond the 60-day reporting requirement lag.…”
Section: Pros and Cons Of Transparencymentioning
confidence: 99%
“…Alternatively, other investors could mimic, with a lag, the positions of the best-performing funds. Notably, Frank, Poterba, Shackelford, and Shoven (2004) demonstrated that copycat portfolios that mimic the disclosed positions of mutual funds generate static returns that are similar to the returns of the actual funds. Wermers, Yao, and Zhao (2007) also found substantial excess returns, even beyond the 60-day reporting requirement lag.…”
Section: Pros and Cons Of Transparencymentioning
confidence: 99%
“…Mimicking is advantageous if a fund can benefit from another fund's security selection without bearing the cost of doing research. Frank et al (2004) show that copycat funds can earn a substantial portion of the return of the fund being copied. The ability to successfully copycat depends on how quickly the private information of the fund manager is incorporated in price.…”
Section: Samplementioning
confidence: 99%
“…Nevertheless, implementing holdings-based approaches has several disadvantages. 2 First, a timely determination of fund activity can be difficult, because fund managers typically disclose portfolio holdings at the latest possible date, otherwise so-called copycat funds could steal a substantial portion of the copied fund's return (see, e.g., Frank, Poterba, Shackelford, & Shoven, 2004;Phillips, Pukthuanthong, & Rau, 2014). For this reason, current legal regulation allows funds to disclose quarterly portfolio holdings with a considerable lag of 60 days (U.S. Securities and Exchange Commission, 2004).…”
Section: Introduction and Literaturementioning
confidence: 99%